The accessibility and utilization of antenatal care clinics in the Capricorn District, Limpopo Province, South Africa - Tladi, F. M. (My University, 2014)
One of the most important factors relating to antenatal care provisions as one of the components of Primary Health Care (PHC) is that they should be easily accessible to all pregnant women for whom these provisions are intended. Accessibility is directly related to the availability, affordability, acceptability, and utilization of the antenatal care clinics by pregnant women. The aim of the study was to explore and describe the factors that influence the accessibility of antenatal care clinics in the rural areas, Capricorn district, Limpopo Province. The researcher used an exploratory, descriptive and contextual design for this approach this study. Data were obtained through interviews with postpartum women, clinic and hospital nurses as well as with nurses from the Maternal and Child Health (MCH) Office in the Provincial Department of Health and Welfare. The results of this research show that several personal and situational factors experienced by both health care users and health care providers have an influence on the accessibility of the antenatal care clinics. Recommendations evolving from this study are that pregnant women, plan their pregnancies, use contraceptives to delay and avoid unplanned and unwanted pregnancies, use the existing clinics and attend regularly.
published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD) Supplement 1:2 (June), 2014, pp. 307-317.
Keywords: Primary health care; Antenatal care; Prenatal care -- south Africa